Open Versus Endoscopic Osteotomy of Posterosuperior Calcaneal Tuberosity for Haglund Syndrome: A Retrospective Cohort Study. Issue 4 (12th April 2021) - Pi, Yanbin; Hu, Yuelin; Guo, Qinwei; Jiang, Dong; Xie, Xin; Zhao, Feng; Chen, Linxin; Ao, Yingfang; Jiao, Chen
Background: Although endoscopic calcaneoplasty and retrocalcaneal debridement have been extensively applied to treat Haglund syndrome, evidence of the value of the endoscopic procedure remains to be fully established. Purpose/Hypothesis: The purpose of this study was to compare the postoperative outcomes and the amount of osteotomy between open and endoscopic surgery for the treatment of Haglund syndrome. It was hypothesized that endoscopic calcaneoplasty would lead to higher patient satisfaction and lower complication rates compared with open surgical techniques. Study Design: Cohort study; Level of evidence, 3. Methods: The following postoperative outcomes were compared between the open surgery group (n = 20) and the endoscopic surgery group (n = 27): visual analog scale for pain, American Orthopaedic Foot & Ankle Society ankle-hindfoot scale, Foot Function Index, Tegner score, Ankle Activity Score, and 36-Item Short Form Health Survey; postoperative complications; and duration of surgery. To determine the extent of resection, the authors compared the calcaneal height ratio, calcaneal resection ratio, calcaneal resection angle, pitch line, and Haglund deformity height between groups. The learning curve for endoscopic calcaneoplasty was also calculated. Results: There were no significant differences between the open and endoscopic groups on any outcome score. Two patients in the open group reported temporary paresthesia around the incisional site, indicating sural nerve injuries; no complication was reported in the endoscopy group. None of the parameters for extent of resection were statistically significant between the groups. The duration of surgery was 44.90 ± 10.52 and 65.39 ± 11.12 minutes in the open and endoscopy groups, respectively ( P = .001). Regarding the learning curve for endoscopic calcaneoplasty (6 surgeons; 27 follow-up patients; 9 patients lost to follow-up), the duration of surgery reached a steady point of 55.68 ± 4.19 minutes after the fourth operation. Conclusion: The results of this study indicated that the endoscopy procedure was as effective as the open procedure. The endoscopic procedure required significantly more time than the open procedure, and the duration of the endoscopic procedure was shortened only after the fourth operation, suggesting that it requires high technical skills and familiarity with the anatomic relationships.